2018
DOI: 10.1042/bsr20180382
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow alteration following acute myocardial infarction in mice

Abstract: Heart failure is associated with low cardiac output (CO) and low brain perfusion that imposes a significant risk for accelerated brain ageing and Alzheimer’s disease (AD) development. Although clinical heart failure can emerge several years following acute myocardial infarction (AMI), the impact of AMI on cerebral blood flow (CBF) at early stages and up to 30 days following MI is unknown. Sixteen months old male mice underwent left anterior descending (LAD) coronary artery ligation. Hemodynamics analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
0
11
0
5
Order By: Relevance
“…Interestingly, Alzheimer’s disease mice also showed increased amyloid levels in cerebral vessels and brain tissue [ 10 ]. Similar vascular-related mechanisms contribute to the increased risk of dementia associated with traumatic brain injury and several age-related conditions like myocardial infarction and ischemic stroke [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Alzheimer’s disease mice also showed increased amyloid levels in cerebral vessels and brain tissue [ 10 ]. Similar vascular-related mechanisms contribute to the increased risk of dementia associated with traumatic brain injury and several age-related conditions like myocardial infarction and ischemic stroke [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding a decreased CBF in HF, a reduction of CBP showed a strong positive correlation with a lower cardiac output, and these parameters were inversely associated with the infarct size in mice with MI. 45 In a clinical study, CBF was reduced in HF patients for approximately 30%, 46 and it principally found in temporal, parietal and occipital regions, particularly in the bilateral prefrontal, frontal, temporal and occipital cortex, thalamus, cerebellum, corona radiate, corpus callosum, hippocampus and amygdala. 10 Previous studies reported that 50% reduction of CBF are expected to cause cognitive change, whereas a sustain reduction in CBF around 20%-30% impaired cognitive function in particular to spatial memory and attention.…”
Section: Potential Molecular Mechanisms Involving In Cognitive Impairment Following Hfmentioning
confidence: 99%
“…HF usually develops following MI and leads to both the impairment of cardiac contractility and the reduction of systemic blood flow to other vital organs including the brain. 10,11 Cerebral hypoperfusion has been observed in animal models of HF, 12,13 along with cognitive impairment and reduction in dendritic spine density. [7][8][9]14 During cerebral hypoperfusion, nutrients, oxygen and chemical energy are suppressed, leading to reactive oxygen species (ROS) overproduction, brain mitochondrial dysfunction and brain cell death, which contributes to reduce brain function, particularly synaptic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial infarction (MI) has been associated with cognitive impairment [1,2]. Previous studies have shown that cerebral blood flow decreases at the onset of MI and remains lower than baseline for 30 days [3]. Increased reactive oxygen species (ROS) were interconnected between cardiac and brain [4].…”
Section: Introductionmentioning
confidence: 99%